PENGARUH HUKUM WARIS ISLAM TERHADAP PELAKSANAAN WARIS ADAT ACEH (STUDI DI ACEH UTARA) - RISKA RISKA (PREMISE LAW JURNAL, 2016)
The mechanism of the inheritance division of the customary communities of Aceh Utara is implemented in accordance with the results of the meetings and discussions among the heirs. When there is a dispute in distributing the inheritance, it is resolved through several steps, firstly through family meetings, secondly through Gampong (village) level, thirdly, through Mukim level (Village Union). If it cannot be resolved through meetings and discussions (customary), it will be solved by Sharia Court. Acehnese tend to divide the inheritance according to customary law than to resolve it in the Sharia Court because if a problem is resolved in the Sharia Court, it will cause a disharmony among the heirs, and it takes quite long time and high cost. The issuess raised in this study were how would the mechanism of the implementation of inheritance division be, how Islamic inheritance law influences the implementation of the customary inheritance of the communities in Northern Aceh, and why the communities in Northern Aceh tend to divide inheritance according to customary law than to resolve it in Sharia Court. It uses judicial empirical approach with descriptive analysis. The data are systematically analyzed using qualitative method, namely the analysis of which a conclusion can be drawn inductively and deductively so that solutions to the problems can be gained. Keywords: Influence of Islamic Inheritance Law, Implementation of Customary Inheritance Law Aceh Utara